Catheter-Based Trans-Epidural Approach to Aspirate Cervical and Thoracic Epidural Abscesses: A Cadaveric Feasibility Study - Qureshi, Adnan I.; Qureshi, Mushtaq H.; Malik, Ahmed A.; Jadhav, Vikram; Kim, Stanley H. (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2015)
Background Approaching and aspirating cervical and high thoracic epidural abscesses through a trans-epidural route from the lumbar region access represents an alternative method for selected patients.Objective We determined the feasibility of catheter-based manipulation and aspiration using the trans-epidural route.Material and Methods A custom designed infusion-suction catheter system that includes an outer suction catheter and inner infusion catheter in concentric relation with radio-opaque marker bands was tested in a cadaveric preparation to determine (1) the ability to place an aspiration catheter over a guidewire using a percutaneous approach within the posterior lumbar epidural space; (2) the highest vertebral level a catheter can be advanced within the epidural space; and (3) the ability to aspirate artificial purulent-like material placed in the cervical and thoracic level epidural space.Results We were able to advance two infusion-suction catheter systems from a 14G Touhy spinal needle inserted via an oblique parasagittal approach at the L2–L3 intervertebral space. The infusion-suction catheter was advanced up to the level of the cervical vertebral level of C2 within the epidural space under fluoroscopic guidance. We were able to aspirate artificial purulent-like material directly injected with a 22G Quincke spinal needle at vertebral levels C4–C5 and at vertebral levels T10–T11 by aspiration and manipulation of the outer catheter within the epidural space at levels C3–C7 andT9–L1, respectively.Conclusions Our observations support the further exploration of a percutaneous catheter-based trans-epidural approach to treat epidural abscesses. The trans-epidural approach may be used alone or as a staged or concurrent approach with open surgical treatment.
Keywords: catheter; cervical vertebra; epidural abscess; microcatheter; thoracic vertebra